Ethics of technology and design ethics in socio-technical systems : Investigating the role of the designer - Fiore, Eleonora (FormAkademisk, 2020)
This paper addresses many of the issues deriving from both design activity itself and the introduction of technology into everyday life. Relevant authors like Papanek (1984), Thackara (2005) and Manzini (2006) warned about the risks of design activity, as well as the consequences of bringing products to the world. Papanek defined design as the second most harmful profession one can practice, while Thackara claims that design is the cause of many troubling situations in our world (Mink, 2016). Manzini advocates the imminent need for a paradigm shift towards both a more sustainable design and way of living. In , Papanek pointed out that designers have a social and moral responsibility for the consequences of their innovations (Mink, 2016). For this reason, first we cannot ignore the advice, but also, we genuinely believe that designers should include ethical principles in their education. This paper seeks to address design ethics focusing on socio-technical systems and the new challenges introduced by both the Internet of things and artificial intelligence. The methodological framework combines the developed in human computer interaction () and computer ethics with a methodology based on need, requirements and performances developed in architecture. This approach is applied to the development of connected appliances, to conduct our reflections on an applied case study. Some guidelines are drawn at the end of this paper to guide designers in achieving a greater understanding of the ethical implications involved in the design process, establishing the responsibilities and limits of the designer.